"أثر التخطيط الاستراتيجي على الأداء المالي في المؤسسات دراسة حالة لوكالات بنكية – ولايتي الوادي والمغير– " - ايمان, طواهرية; صبرية, هبيتة; منال, قطاري; فريال, سنيقر (University of eloued جامعة الوادي, 2021)
" لقد قمنا من خلال هذه الدراسة بإبراز أثر التخطيط الاستراتيجي على الأداء المالي وكان الغرض من ذلك هو محاولة التعرف بنوع من الدقة على ماهية التخطيط الاستراتيجي في المنظمات , وما المقصود بالأداء المالي وكذا مؤشراته ومعاييره , خاصة وأن الممارسة الجدية للتخطيط الاستراتيجي بمختلف مراحله تسمح للمنظمة بتوع المستقبل واستشرافه والاعداد له لاتخاذ القرارات على أساسه , لتنتهي الى الخيارات الاستراتيجية الملائمة والتي تسمح لها بالتأقلم والتكيف مع بيئتها الداخلية والخارجية ,ولتحديد الكيفية التي يتم فيها قياس مستوى النجاح في تحقيقه , كان من الضروري استحداث نظام ادارة يمكن المنظمة من رؤيتها الى واقع عملي من خلال مراقبة وضبط وتقييم الخطط وتوضيح مواطن القوة والضعف في عملياتها الداخلية والخارجية بما يساعد في تحسين وتطوير الأداء المالي . لذلك كان موضوع التخطيط الاستراتيجي الذي يمثل جزءا مهما من العملية الادارية من أكثر المواضيع أهمية وبروزا وتجددا في عالم الادارة في الآونة الأخيرة باعتباره عملية مستمرة تتعلق بالمستقبل تقوم على التوقعات البيئة الخارجية والداخلية ,ومستويات الأداء في الماضي والحاضر والمستقبل , وتقييم الفرص والمخاطر عن طريق تطوير الأهداف والاستراتيجيات والسياسات والخطط التنفيذية. وبناء على الدراسة الميدانية التي قمنا بها حول التخطيط الاستراتيجي وأثره على الأداء المالي في المؤسسة محل الدراسة (بعض الوكالات البنكية بولايتي الوادي والمغير ) , فقد خلصت الدراسة لمجموعة من النتائج وذلك من خلال البيانات التي جمعها الباحث من الاستبيان قام بها , وتم عرض وتفسير النتائج وربطها بالدراسات السابقة ذات العلاقة . من خلال الدراسة يمكن أن نحصل على جملة من النتائج النظرية وكذا الميدانية , وهذا من خلال نتائج الدراسة الميدانية من أجل نفي أو تأكيد صحة الفرضيات المطروحة في الدراسة ""We have, through this study, highlighted the impact of strategic planning on financial performance, and the purpose was to try to identify with some kind of accuracy what strategic planning is in organizations, and what is meant by financial performance as well as its indicators and standards, especially since the serious practice of strategic planning in its various stages allows the organization to educate the future Foreseeing it and preparing for it to take decisions on its basis, to end up with the appropriate strategic options that allow it to adapt and adapt to its internal and external environment, and to determine how to measure the level of success in achieving it, it was necessary to develop a management system that enables the organization to see it into a practical reality through monitoring Adjusting and evaluating plans and clarifying the strengths and weaknesses in its internal and external operations, in a way that helps in improving and developing the financial performance. Therefore, the subject of strategic planning, which represents an important part of the administrative process, was one of the most important, prominent and renewed topics in the world of management in recent times as it is a continuous process related to the future based on external and internal environment expectations, performance levels in the past, present and future, and evaluating opportunities and risks by developing goals. strategies, policies and operational plans. Based on the field study that we conducted on strategic planning and its impact on the financial performance of the institution under study (some banking agencies in the wilayats of Al-Wadi and Al-Mughayyir), the study concluded a set of results through the data collected by the researcher from the questionnaire he conducted, and the results were presented, interpreted and linked. related previous studies. Through the study, we can obtain a number of theoretical as well as field results, and this is through the results of the field study in order to negate or confirm the validity of the hypotheses put forward in the study."
ماستر ادارة اعمال
Keywords: التخطيط الاستراتيجي ،الاداء المالي، الادارة; Strategic planning, financial performance, management